The Influence of B Cell Depletion Therapy on Naturally Acquired Immunity to Streptococcus pneumoniae - Ercoli, Giuseppe; Ramos-Sevillano, Elisa; Nakajima, Rie; de Assis, Rafael Ramiro; Jasinskas, Algis; Goldblatt, David; Felgner, Philip; Weckbecker, Gisbert; Brown, Jeremy (Frontiers in Immunology, 2021)
Treatment with the anti-CD20 antibody Rituximab to deplete CD20+ B cells is an effective treatment for rheumatoid arthritis and B cell malignancies, but is associated with an increased incidence of respiratory infections. Using mouse models we have investigated the consequences of B cell depletion on natural and acquired humoral immunity to Streptococcus pneumoniae. B cell depletion of naïve C57Bl/6 mice reduced natural IgM recognition of S. pneumoniae, but did not increase susceptibility to S. pneumoniae pneumonia. ELISA and flow cytometry assays demonstrated significantly reduced IgG and IgM recognition of S. pneumoniae in sera from mice treated with B cell depletion prior to S. pneumoniae nasopharyngeal colonization compared to untreated mice. Colonization induced antibody responses to protein rather than capsular antigen, B cell depletion prior to colonization reduced this response, as observed measuring serum levels of IgG to several protein antigens by protein array. However, B cell depleted S. pneumoniae colonized mice were still partially protected against both lung infection and septicaemia when challenged with S. pneumoniae after reconstitution of their B cells. These data indicate that although B cell depletion markedly impairs antibody recognition of S. pneumoniae in colonized mice, some protective immunity is maintained, perhaps mediated by cellular immunity.